Apitoxin harvest impairs hypopharyngeal gland structure in Apis mellifera honey bees - Bovi, Thaís S. [UNESP]; Onari, Paula [UNESP]; Santos, Sérgio A. A. [UNESP]; Justulin, Luis A. [UNESP]; Orsi, Ricardo O. [UNESP] (Springer Nature, 2017)
Apitoxin harvesting is a stressful practice for honey bees Apis mellifera L. due to the release of alarm pheromones that alter communication and behaviour and may also affect their physiology. Thus, the goal of this research was to verify the effects of apitoxin harvesting on the development of the hypopharyngeal glands (HGs), evaluating the number and area of acini. For this, ten beehives were subjected to one of two treatments: T1, without apitoxin harvest and T2, with apitoxin harvested by an electric collector. We collected ten 6-day-old honey bees in each treatment once every month (October through December). The HGs were removed and were processed for morphological-stereological analysis. The worker bees from hives subjected to treatment T2 showed a smaller acinar area and lower number of acini than those from hives subjected to treatment T1. Thus, apitoxin harvest negatively affects the structure of the hypopharyngeal glands, consequently affecting the production of royal jelly.
Keywords: apitoxin; beekeeping; hypopharyngeal glands; morphology; nutrition